ENHANCING MOBILE CRYPTOCURRENCY WALLETS: A COMPREHENSIVE ANALYSIS OF USER EXPERIENCE, SECURITY, AND FEATURE DEVELOPMENT - Richard Richard; Muhammad Ammar Marsuki; Gading Aryo Pamungkas; Felix Irwanto (LPPM Nusa Mandiri, 2024)
The surge in cryptocurrency usage has increased reliance on cryptocurrency wallet applications. However, the usability, security, and feature richness of crypto wallets require significant enhancements. This research aims to identify critical factors that should guide the future design of mobile cryptocurrency wallets. The first step was to collect user reviews on several popular crypto wallets as the dataset. A total of 5,466 mobile wallet-related reviews from mobile application stores were filtered and analyzed. A machine-learning approach was used to cluster the user reviews. The analysis shows that customer issues are divided into four main themes: domain-specific challenges, security and privacy concerns, misconceptions, and trust issues. A software process assessment was also conducted to examine the current state of crypto wallets in terms of security, usability, and feature richness. Around 21 crypto wallet platforms were explored and assessed. Based on the thematic analysis and software process assessment, feature recommendations are proposed to address these shortcomings and enhance the credibility of mobile cryptocurrency wallets.